(untitled) (Annals of Medical Research, 2021)
Aim: The purpose of our study was to determine the rate of anemia and iron store status in Turkish elementary school children. Materials and Methods: We included 1296 children applied to pediatrics department of a large teaching hospital and evaluated the hemoglobin, iron, unsaturated iron binding capacity and ferritin levels. Results: The results showed that 9.88% of the children had anemia and 1.62% had iron-deficiency anemia. Despite the normal Hemoglobin (Hb) levels, the ratio of children with low ferritin levels was found to be 36.49%, suggesting that children with normal Hb levels might not be having adequate level of iron stored. The Hb levels were found to be significantly lower in the group of 6- and 7-year old children when compared to other ages. Conclusion: Being an elementary issue for normal growth and academic success in school, iron status should be closely monitored in school children. Additionally, different age groups have different needs for iron supplementation; therefore contemporary guidelines for the management of anemia in children should be established by authorities.